IMPLEMENTING AUGMENTED REALITY (AR) AS AN INTERACTIVE TOOL FOR MASTERING MARITIME ENGLISH IN ENGINEERING TOOLS LEARNING - Alberto; Mutmainnah Hasyari; Muhammad Tri Pujianto; Muh Irsan (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2026)
Mastering Maritime English, particularly technical terminology related to engine tools, is essential for marine engineering cadets to support effective onboard communication and operational safety. However, traditional instructional methods often fail to help cadets visualize, retain, and accurately pronounce complex technical vocabulary.Despite the growing integration of Augmented Reality (AR) in education, limited studies have specifically explored its application in Maritime English learning for engineering tools.  Therefore, this study aimed to design and implement an AR-based interactive learning product to enhance cadets’ understanding, engagement, retention, and pronunciation accuracy in Maritime English learning. This study employed a mixed-methods approach involving 25 second-semester Marine Engineering cadets at the Merchant Marine Polytechnic of Makassar selected through purposive sampling. Quantitative data were collected through Likert-scale questionnaires, while qualitative data were obtained through classroom observations and semi-structured interviews exploring cadets’ learning experiences, cognitive engagement, and interaction with the AR application. The findings revealed that the AR-based learning product significantly improved cadets’ learning experiences and technical vocabulary mastery. The product integrated 3D visualization, audio pronunciation, and interactive features that enabled cadets to better understand and memorize engine tools terminology. Quantitative results showed high average scores in effectiveness and pronunciation accuracy (4.56), retention (4.52), and engagement (4.43). Qualitative findings further demonstrated that AR promoted active participation, self-directed learning, and repeated pronunciation practice through immersive interaction. This study contributes to Maritime English pedagogy by providing an innovative and contextualized AR-based learning approach specifically designed for technical engine tools terminology. The findings suggest that AR can bridge the gap between theoretical Maritime English instruction and practical technical understanding in maritime education.